IMPORTANT ASPECTS OF ATTACK ACTIONS IN BEACH VOLLEYBALL - Gabriel Alexandru PETROVICI; Zoltan KOVACS (Editura Universităţii din Oradea, 2021)
The game of beach volleyball has developed over the past years to become more spectacular with game actions that can leave the audience speechless, explosive players, attack and defense actions that can capture the attention of spectators for a long time. Spiking is a fundamental skill in both indoor and beach volleyball, being appreciated by the public as one of the most spectacular moves in beach volleyball, but also is appreciated by coaches as the most efficient modality of obtaining points. The present paper tries to identify the essential aspects of attacking actions: entering the attacking position, anticipating the setting and adapting to it, detachment step for attack, the arms swing, the heel-toe-finger movement, the "bow and arrow" attack movement.